2005
DOI: 10.1242/jcs.01631
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin takes the lead

Abstract: Cofilin has emerged as a key regulator of actin dynamics at the leading edge of motile cells. Through its actinsevering activity, it creates new actin barbed ends for polymerization and also depolymerizes old actin filaments. Its function is tightly regulated in the cell. Spatially, its activity is restricted by other actin-binding proteins, such as tropomyosin, which compete for accessibility of actin filament populations in different regions of the cell. At the molecular level, it is regulated by phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
254
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(268 citation statements)
references
References 90 publications
10
254
1
3
Order By: Relevance
“…It has been shown that activated PAK1 phosphorylates LIMK1 (46) and that phosphorylated LIMK1 phosphorylates cofilin (i.e. inactivates cofilin), which decreases its actin depolymerizing activity (47,48). In addition, we found that phosphorylations of LIMK1 and cofilin are induced by glucose stimulation in MIN6-K8 ␤-cells.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been shown that activated PAK1 phosphorylates LIMK1 (46) and that phosphorylated LIMK1 phosphorylates cofilin (i.e. inactivates cofilin), which decreases its actin depolymerizing activity (47,48). In addition, we found that phosphorylations of LIMK1 and cofilin are induced by glucose stimulation in MIN6-K8 ␤-cells.…”
Section: Discussionsupporting
confidence: 50%
“…PAK1 activates LIM kinase 1 (LIMK1) by its phosphorylation (46), which phosphorylates cofilin at serine 3. Phosphorylation of cofilin (inactive form) inhibits its actin depolymerizing activity by binding to actin monomers (47,48). Dephosphorylated cofilin (active form) increases the rate of actin depolymerization and maintains a pool of actin monomer (33).…”
Section: N-wasp Mediates Glucose-induced Actin Dynamics-al-mentioning
confidence: 99%
“…downstream of RhoA, during different stages of cell migration is necessary to finetune actin reorganization and polymerization events, providing the basis for altering cell motility. As proposed previously (8,9), cofilin has important functions in controlling the initial directional response of cells after sensing a chemotactic gradient. Cofilin severs old filaments replenishing the G-actin pool of cells and it generates new "free barbed ends" after being recruited to the active polymerization zone at what will become the leading edge of cells oriented toward a growth factor gradient (7).…”
Section: Discussionmentioning
confidence: 63%
“…By severing actin filaments, cofilin increases both the availability of G-actin monomers as well as the number of "barbed ends" for polymerization (7). Furthermore, severed filaments are the preferred substrate for dendritic nucleation by the Arp complex (8,9). Localized induction of actin polymerization and the formation of branched actin networks constitute the basis for membrane protrusion and cell motility (2,10,11).…”
mentioning
confidence: 99%
“…40,41 Ras-transformed cells demonstrate actin cytoskeleton disorganization and severing of F-actin. 42 We have earlier shown total severing of F-actin in rat E1A + cHa-Ras cells. 43 mERas-Waf1 +/+ cells respond to NaB treatment by accumulation of focal adhesions and appearance of F-actin, which drives changes in cell shape that are important for a variety of morphogenetic events, including cell migration.…”
Section: Waf1mentioning
confidence: 92%